Framing of Eco-Discourse in Social Media - Radha Andhra Swari; Made Sani Damayanthi Muliawan; Ni Kadek Dea Arisinta; Ni Luh Made Manik Yuliasih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
In this digital era, social media such as Instagram certainly plays an important role in promoting sustainable actions that can attract the attention of its users. Visual content that depicts strategically-framed messages about sustainability has the potential to influence people's perspectives and may lead to social change. This study aims to analyze the framing of eco-discourse in Kembali Becik and Astungkara Way through Instagram. In addition, this study also aims to discuss solutions related to sustainable actions offered by the two forums. This study was designed using a qualitative descriptive method. The results revealed that positive and negative framing can be found in both accounts.